2012
DOI: 10.1002/ajhb.22327
|View full text |Cite
|
Sign up to set email alerts
|

Dietary diversity score is a useful indicator of vitamin A status of adult women in Northern Kenya

Abstract: Our results indicate that diversified diets enhance vitamin A status relative to narrower diets with equivalent vitamin A content. DDS shows a potential as a low-cost, field-friendly method for exploratory assessments of vitamin A status, and a potential as a research tool for human biologists and anthropologists interested in dietary quality and micronutrient health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 42 publications
0
14
1
Order By: Relevance
“…Beyond this basic plan, variations were seen in the diversity of ingredients women included in their meals (Fujita et al, 2012). For example, those who were less fortunate took their morning tea without milk.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond this basic plan, variations were seen in the diversity of ingredients women included in their meals (Fujita et al, 2012). For example, those who were less fortunate took their morning tea without milk.…”
Section: Discussionmentioning
confidence: 99%
“…Study had reported that DDS is well correlated with serum retinol level and could predict vitamin A deficiency (23). …”
Section: Discussionmentioning
confidence: 99%
“…indicators [13][14][15], the strength of our study was the possibility to examine two seasons with different food consumption patterns. Indeed, our results suggest that the associations between dietary diversity and micronutrient status may vary from season to the other -we found a seasonal discrepancy in the association between dietary diversity and zinc.…”
Section: Compared With Earlier Reports On the Associations Between DImentioning
confidence: 99%
“…Indeed, previous studies in pregnant women in Southern Ethiopia [13] and breastfeeding women in Northern Kenya [14] have found that women with a low DDS had an increased risk of having vitamin A deficiency compared to women with a higher DDS. Furthermore, the Ethiopian researchers also found an association between DDS and serum zinc among pregnant women [15].…”
Section: Introductionmentioning
confidence: 97%